An Analysis of Written and Spoken Discourse in English Assignment and Classroom Discussion - Aqielah, Aqielah; Hidayat, Didin Nuruddin; Alek, Alek; Ersyad, Zakila Mardatila (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
This study analyzed the students’ written and spoken discourse in English class about the material of congratulating people. In daily conversation, students have informal conversations. However, when it turns to discussion, they sometimes use formal forms of language even when talking to other students. Therefore, this study aims to find the types of formal language forms used by students during the discussion and the purposes of the use. The participants of this study are the eighth-grade students divided into four groups. A qualitative descriptive approach is applied in this study, and the data are analyzed with IRF. From the analysis, the students used formal forms of language in four types: neutral lexis, complete form, politeness, and turn-taking. This study observes the discussion between the students and how the students interact with each other, as well as whether there is some social problem within the class. Another perception from the researchers is that students need to be motivated to speak English more during English class, even if they are discussing with their friends or when they ask questions to the teacher